Readiness towards Self Directed Learning among Undergraduate Students in Teaching Hospital, Jumla - Maharjan, Ramu; Verma, Ruchi (Nepal Journal of Health Sciences, 2026)
Introduction: Self-directed learning (SDL) means self-managed learning that plays important role in facilitating adult learning and upgrading knowledge and skills of individual’s independently. Readiness for SDL implies that the learners are responsible for their own learning through a student-centered learning method. SDL strategies empower students to handle their academic work effectively and adapt to challenging situations.Objective: To assess the readiness toward self-directed learning among undergraduate students in teaching hospital Jumla.Methods: A cross-sectional study was conducted among 277 undergraduate students of Karnali Academy of Health Sciences (KAHS) using total enumerative sampling technique to select sample. Self-Directed Learning Readiness Scale (SDLRS) tool was used to collect the data. All collected data was analyzed using descriptive statistics and inferential statistics.Result: This study finding revealed that majority (72.9%) of undergraduate students had high level of readiness towards SDL whereas more than one fourth (27.1%) have low level of readiness. There was statistically significant association between level of readiness towards SDL and age (p=0.003), academic program (p=0.004), and academic year (p=0.018).Conclusion: It is concluded more than one fourth of the KAHS undergraduate students had low level of readiness towards SDL. These results suggest need to implement strategies that strengthen student’s readiness for SDL, with particular attention to areas on subscales where students scored comparatively lower such as self-management and self- control.